I will see you in Seattle Celia Mine - Elwell, Robert Sanders, Zellah E.
For voice and piano Front cover contains the text, "the Alaska-Yukon-Pacific-Exposition 1909," and, "President Chilberg (to whom this song is dedicated)". Decorative border and designs embellishing the text, photographs of President Chilberg and the A.-Y.-P. Fair Grounds with the caption, "President Chilberg (to whom this song is dedicated) and the A.-Y.-P. Fair Grounds. Black print.